Preliminary Recommendations for Effective Tobacco Tax Design in Bangladesh - World Bank (World Bank, Washington, DC, 2018)
The key issues and challenges for effective tobacco tax design in Bangladesh, Tobacco control poses a major public policy concern and challenge in Bangladesh, which has one of the world’s highest rates of tobacco use. Low cigarette taxes and prices have contributed to an alarming expansion in consumption. A complex tax structure assists in keeping cigarette prices low in Bangladesh. Current taxation policy does not achieve the dual objective of discouraging consumption and maximizing revenue. Extensive evidence from across the world clearly shows that tax-induced price increases of cigarettes and other tobacco products are highly effective in curbing tobacco use. It is recommended that Bangladesh implement a unitary specific rate for cigarettes in the long run.